Analysis of the Adequacy of Science Materials for Primary School Learners in Phase A Based on the Merdeka Curriculum - Yumna, Silka; Yusuf Muslihin, Heri; Hamdu, Ghullam (Journal of Innovation and Research in Primary Education, 2025)
This study is a literature review aimed at analyzing the adequacy of science learning materials for Phase A elementary school students (grades 1 and 2) in the context of implementing the Kurikulum Merdeka (Independent Curriculum). The background of this research stems from significant changes in Indonesia’s education system through the introduction of the Independent Curriculum, which emphasizes contextual, flexible, and student-centered learning. This approach is also applied to science education at the early primary level, a critical stage in building children’s foundational scientific literacy. The method used in this study is a literature review, with data collected through the identification, search, and selection of various relevant sources such as curriculum documents, textbooks, scholarly articles, and expert opinions. The data were analyzed qualitatively using content analysis and literature synthesis, focusing on aspects such as the definition, structure, breadth, depth, and relevance of the science material, as well as its potential strengths and weaknesses. The results indicate that the science materials for Phase A in the Independent Curriculum show promising potential, particularly through thematic integration and an exploratory approach that aligns with children's developmental stages. However, several challenges remain, including limited conceptual depth, the crucial role of teachers, the availability of learning resources, and the need for holistic assessment tools. In conclusion, the Independent Curriculum provides a positive direction for science learning in Phase A. However, collaboration among various stakeholders is necessary to ensure the adequacy and effectiveness of the materials in building strong scientific literacy from an early age.